Development of Digital Media to Strengthen Family of Generation Alpha in the Thai Context - Nilrungratana, Pitchaya; Deewai, Anusara; Pattrawiwat, Kanchana; Tuntivivat, Sudarat (Journal of Cultural Analysis and Social Change, 2026)
The objective of this research is to develop and evaluate the effectiveness of digital media in strengthening the generation of alpha families in the Thai Context. The sample is parents of Generation Alpha children, 532 people, who were obtained from Stratified Random Sampling from all regions of Thailand. Data were collected from the questionnaire on 5 5-point rating scale. The level has a classification power value between .266 and .898 and has a coefficient Cronbach’s alpha equal to .937. The data was analyzed using a needs assessment and a Priority Needs Index Modified (PNIm). The digital media performance assessment tool is the children's media development expert's performance assessment form from 3 people, and the satisfaction assessment for using digital media from 20 families with a generation of alpha children. The results showed that: 1) the reality of family strength in Generation Alpha in the Thai context is very high ( = 3.94), the expected conditions of family strength in Generation Alpha in the Thai Context are at the highest level ( = 4.87), and the necessary needs (Modified Priority Needs Index: PNImodified) of family strength of Generation Alpha in the Thai context is 0.21-0.26. The most urgent need is positive relationships within the family (0.26). This is followed by mental immunity and adaptation to technology and the digital world (0.25), roles and responsibilities of parents (0.23), and molding and enhancing good characteristics (0.21), respectively. The research results were digital media in the form of a Content Management System (CMS). The results of the effectiveness of digital media on the family strength of Generation Alpha in the Thai context, according to experts, are very high (=4.39) and the results of the assessment of satisfaction with the use of digital media to the family strength of Generation Alpha in the Thai context by families with Generation Alpha children are very high (=4.37). A total of 592 people visited the website between 22 December 2567 and 20 February 2568.